Higher Education: Adaptation and Resources inTimes of Pandemic - Ferreira, Albertina; Santos Coelho, Rosa; Grifo, Anabela (Revista da UI_IPSantarém, 2020)
The COVID-19 pandemic set on significant changes in the families’ routines, namely, the need for a radical and sudden adaptation at all levels of education. Teachers and students were prevented from maintaining their well-known routines. In this sense, there was a need to promote the adjustment, practically instantaneous, from totally face-to-face teaching to a full distance teaching, with the inherent constraints. This study intended to: a) show some of the adaptations made in course units of the Escola Superior Agrária de Santarém; b) analyse the impact on students' academic success, with the adaptation of face-to-face teaching to digital platforms. The results highlight some of the experiences obtained during the period to which the study reports and show that there are no significant differences between the performance of students in classroom teaching and the performance of students in distance learning.